(3GdMhGQ aj GdCSQI cYGed eDKQ Ydi TNUjI GdeQGgb aj Uaha GdeQMdI GdeJhSWI (B(12-16 (3SfI(B)s - (3ZhQS, dhQs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2013)
(3JJfGhd gPg GdOQGSI ehVhY GdMhGQ GdCSQj GdPj jYO ef Cge hSGFd GdGJUGd GdaYGdI hGdJj JMbb fJGFL faSjI hJQHhjI hGLJeGYjI EjLGHjI(B. (3hbO JeMhQJ CSFdI GdOQGSI Mhd eG jdj(B: 1) (3dCj eOi jecf dGNJdGa GdBQGA hCSGdjH GdJQHjI GdCSQjI Cf Jchf SHHG aj YOe GdJhGab Hjf GdeQGgb hhGdOjg? (B2) (3dCj OQLI JMJGL GdCSQI Edi GdMhGQ MJi JUd Edi fJjLI JQVj GdeQGgb? (B3) (3Edi Cj eOi jecf Cf fUd eY GdeQGgb Edi MhGQ CSQj eSJeQ? (B4) (3dCj eOi jchf GdMhGQ GdCSdhH GdCeKd aj GdeQGgbI? (B5) (3dCj OQLI jbdd GdMhGQ eY GdeQGgb ef EMHGWg hbdbg hGVWQGHg? ESJNOeJ gPg GdOQGSI GdefgL GdGSJcTGaj GdPj jgOa Edi eYQaI eOi JCKjQ GdMhGQ GdCSQj Ydi TNUjI eLehYI ef GdJdGePI GdeQGgbjf ef NdGd JeQjQ GSJeGQI dLeY eYdheGJ Mhd gPG GdehVhY(B. (3Jqe GdGYJeGO dgPG GdZQV Ydi GdGSJeGQI GdeZdbI GdehLgI Edi (B50 (3JdejPG ef JdGePI GdeQMdI GdeJhSWI GdPjf JJQGhM CYeGQge Hjf Gd(B12 (3h(B16 (3SfI ef PchQ hEfGK HZjI GdJYQa Ydi eOi CgejI GdMhGQ aj GdCSQI(B. (3CeG GdebGHdGJ eY CgGdj GdeQGgbjf acGfJ HgOa GdJYQa Ydi QCjge ef MjK JYGedge eY GdeQGgb hYdGbJge Hg(B. (3HYO JMdjd GdGSJeGQGJ hGdebGHdGJ JHqjf Cf YOOkG cHjQkG ef GdJdGePI jYGfhf ef eTcdGJ hUQGYGJ CSQjI MjK dG ecGf ddMhGQ OGNd GdCSQI, hbO CLeY eYXe GdJdGePI Ydi Cf GdCgd dG jagehfge ajdLDhf Edi GdJTGLQ eYge, ceG Cf GdCgd jdLDhf Edi GdJCfjH YhVG Yf GdMhGQ hGdefGbTI hgPG eG jSHH GdYOhGfjI YfO GdJdGePI(B. (3Ydi VhA gPg GdfJGFL Je GbJQGM HQfGeL JhLjgj EQTGOj NGU HgPg GdeLehYI ef eQGgbj GdUa GdSGHY hGdKGef hGdJGSY CSGSj(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Adolescents; Adolescents; Cycle moyen; Education Familiale; Family education; Intermediate Education; (3GdJQHjI GdGSQjIs; (3GdeQGgbhfs; (3GdeQMdI GdeJhSWIs